Urgensi Kompetensi Guru Dalam Pembelajaran Alquran Di Raudhatul Athfal Kota Medan - Lubis (UMSU, 2020)
This study aims to determine the activities of the Ministry of Religion in Medan in order to improve and strengthen teacher competence in teaching the Koran, related to learning planning, learning methods used, obstacles encountered, and efforts made by teachers in overcoming obstacles in teaching the Koran in Raudhatul Athfal City of Medan. The research method used is qualitative research The data collection techniques are interviews, observation, documentation study. Then, data management consists of data reduction, data display / data presentation, data analysis, techniques guaranteeing the validity of research results. The results of the study revealed that the activities of the Ministry of Religion in Medan in increasing teacher competence in teaching the Koran in Raudhatul Athfal Medan City, were pursued by carrying out programs to improve teacher education qualifications, integrated competency-based training programs, educational supervision programs and teacher training empowerment programs, carried out continuously. Learning planning conducted by Raudhatul Athfal teacher in teaching Koran in Raudhatul Athfal Medan City, namely planning for compiling or organizing learning materials that will be given / taught to students consisting of (1) planning for Semester Program (PROMES), (2 ) Weekly Learning Implementation Plan (RPPM), (3) Daily Learning Implementation Plan (RPPH), and (4) Standard Operating Procedure (SOP). The Koran Learning Method used by teachers in general in the city of Medan, namely using the Iqro method 'which consists of letter recognition, harakah recognition, letter connection, short length recognition, and sentence recognition, recognition of waqaf signs.